1988
DOI: 10.1017/s0031182000066737
|View full text |Cite
|
Sign up to set email alerts
|

Extravascular foci ofTrypanosoma vivaxin goats: the central nervous system and aqueous humor of the eye as potential sources of relapse infections after chemotherapy

Abstract: Relapse of parasitaemia after drug treatment of trypanosome infection is normally attributed to drug-resistance on the part of the parasite, under-dosage of the drug or reinfection of the host. In addition, inaccessibility of parasites to drug through sequestration in privileged extravascular sites has been shown in the past to occur with Trypanosoma brucei, and we have obtained evidence that extravascular foci of T. vivax can also serve as a source of relapsing infections. Infection of goats with a West Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
8

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 21 publications
2
29
0
8
Order By: Relevance
“…Paiva et al (2000) believe that adaptation to the mechanical transmission has decreased antigenic variation of VSG, however Dagnachew et al (2015) observed that T. vivax strains from areas without tsetse (only mechanical transmission occurs) are as pathogenic as those from areas with cyclical transmission. Another explanation for the persistence of the infection is refuge points with subsequent lapses in infection such as cerebrospinal fluid and aqueous humor (WHITELAW et al, 1988). The presence of T. vivax in the cerebrospinal fluid was observed and correlated with central nervous system damage in chronically infected goats.…”
Section: Discussionmentioning
confidence: 97%
“…Paiva et al (2000) believe that adaptation to the mechanical transmission has decreased antigenic variation of VSG, however Dagnachew et al (2015) observed that T. vivax strains from areas without tsetse (only mechanical transmission occurs) are as pathogenic as those from areas with cyclical transmission. Another explanation for the persistence of the infection is refuge points with subsequent lapses in infection such as cerebrospinal fluid and aqueous humor (WHITELAW et al, 1988). The presence of T. vivax in the cerebrospinal fluid was observed and correlated with central nervous system damage in chronically infected goats.…”
Section: Discussionmentioning
confidence: 97%
“…Animals recovering from the disease can become reservoirs, with low or even undetectable blood levels of the parasite (Plata 1931b). In the aparasitemic phases, trypanosomes can be found extravascularly, in lymph nodes (Hoare 1972), eyes (in the choroid plexus and aqueous humor) (Whitelaw et al 1988), and cerebrospinal fluid (Tuntasuvan et al 1997). Occult infections can be reactivated by stress.…”
Section: Pathogenesis and Symptomsmentioning
confidence: 99%
“…Tal fato tem grande importância na fisiopatogenia das lesões inflamatórias e degenerativas descritas no coração (Masake 1980) e sistema nervoso (Whitelaw et al 1988) de caprinos infectados experimentalmente por T. vivax.…”
Section: Introductionunclassified
“…vivax já foi identificado no sistema nervoso central, humor vítreo (Whitelaw et al 1988) e miocárdio (Kimeto et al 1990) onde foi apontado como causador de patologias nessas regiões. Entretanto, ainda não se encontrou relatos da presença do parasita no parênquima de órgãos reprodutivos.…”
Section: Introductionunclassified